Brown Tumour in a Patient with Secondary Hyperparathyroidism Resistant to Medical Therapy: Case Report on Successful Treatment after Subtotal Parathyroidectomy - Nicola Di Daniele; Stefano Condò; Michele Ferrannini; Marta Bertoli; Valentina Rovella; Laura Di Renzo; Antonino De Lorenzo (International Journal of Endocrinology)
Brown tumour represents a serious complication of hyperparathyroidism. Differential diagnosis, based on histological examination, is only presumptive and clinical, radiological and laboratory data are necessary for definitive diagnosis. Here we describe a case of a brown tumour localised in the maxilla due to secondary hyperparathyroidism in a young women with chronic renal failure. Hemodialysis and pharmacological treatment were unsuccessful in controlling secondary hyperparathyroidism making it necessary to proceed with a subtotal parathyroidectomy. The proper timing of the parathyroidectomy and its favourable effect on regression of the brown tumor made it possible to avoid a potentially disfiguring surgical removal of the brown tumor.